The Influence of Individual Characteristics and Employee Empowerment on Organizational Commitment with Self-Efficacy as a Moderation Variable - Rizky Dwi Amilovea; Survival; Soedjono (Journal of Management Research and Studies, 2025)
Organizational commitment is an interesting phenomenon because of the importance of a person's commitment to the organization where the individual works. Employee commitment is one of the keys that determines the success or failure of an organization in achieving its goals. Employees who are committed to the organization usually show a work attitude that is attentive to their duties, and they are very responsible for carrying out their duties and are very loyal to the organization. The purpose of this study was to obtain empirical evidence of the influence of individual characteristics and employee empowerment on organizational commitment with self-efficacy as a moderating variable (Study at the Army Polytechnic Kodiklatad in East Java). Data collection using questionnaires or by providing a list of questions to respondents. While for the analysis method using the Structural Equation Model - Partial Least Square (SEM-PLS) with the help of the SmartPLS tool. From the results of the study, individual characteristics are not able to increase organizational commitment. Employee empowerment is able to increase organizational commitment. Self-efficacy is able to increase organizational commitment. Individual characteristics are able to increase organizational commitment moderated by self-efficacy. Employee empowerment is able to increase organizational commitment moderated by self-efficacy.